Characterization of the mitochondrial genomes of two toads, Anaxyrus americanus (Anura: Bufonidae) and Bufotes pewzowi (Anura: Bufonidae), with phylogenetic and selection pressure analyses - Cai, Yu-Ting (PeerJ, 2020)
Mitogenomes are useful in analyzing phylogenetic relationships and also appear to influence energy metabolism, thermoregulation and osmoregulation. Much evidence has accumulated for positive selection acting on mitochondrial genes associated with environmental adaptation. Hence, the mitogenome is a likely target for environmental selection. The family Bufonidae (true toads) has only nine complete and four partial mitogenomes published compared to the 610 known species of this family. More mitogenomes are needed in order to obtain a clearer understanding of the phylogenetic relationships within Bufonidae that are currently controversial. To date, no mitogenomes have been reported from the genera Anaxyrus and Bufotes. Anaxyrus americanus can live in low temperature environments and Bufotes pewzowi can live in high salinity environments. We sequenced the mitogenomes of these two species to discuss the phylogenetic relationships within Bufonidae and the selection pressures experienced by specimens living in low temperature or saline environments. Like other toads, the circular mitogenomes of both species contained the typical 37 genes. Anaxyrus americanus had the highest A+T content of the complete mitogenome among the Bufonidae. In addition, A. americanus showed a negative AT-skew in the control region, whereas Bufotes pewzowi showed a positive AT-skew. Additionally, both toad species had unique molecular features in common: an ND1 gene that uses TTG as the start codon, an extra unpaired adenine (A) in the anticodon arm of trnS (AGY), and the loss of the DHU loop in trnC. The monophyly of Bufonidae was corroborated by both BI and ML trees. An analysis of selective pressure based on the 13 protein coding genes was conducted using the EasyCodeML program. In the branch model analysis, we found two branches of A. americanus and Bufotes pewzowi that were under negative selection. Additionally, we found two positively selected sites (at positions 115 and 119, BEB value > 0.90) in the ND6 protein in the site model analysis. The residue D (119) was located only in A. americanus and may be related to adaptive evolution in low temperature environments. However, there was no evidence of a positively selected site in Bufotes pewzowi in this study.